Research on Collaborative Education Mode of Industry-Education Alliance of Cross-Border E- Commerce In Higher Vocational Colleges Under the Background of Entrepreneurship and Innovation - Xiang, Hongmei (Journal of Theory and Practice of Social Science, 2024)
With the proposal of the employment concept of "mass entrepreneurship and innovation", the cross- border e-commerce industry has entered a stage of rapid development. However, in contrast, the gap of innovative and entrepreneurial cross-border e-commerce talents is getting bigger and bigger. In other words, the growth rate of cross-border e-commerce talents is far lower than the development rate of cross-border e-commerce. Based on this, the cultivation of cross-border e-commerce talents must be put on the agenda as soon as possible.